Immuno-Molecular Diagnosis of Toxoplasma gondii in Blood and Meat of Indigenous Chickens in Some Rural Regions of Iraq - Amal Hassan Abd Al-Shabbani (Journal of Global Pharma Technology, 2019)
Herein the object was to detect the prevalence rate of the parasite Toxoplasma gondii (T. gondii) in blood and meat samples of indigenous chickens. Total of 92 chickens of both sexes of more than one year old were selected from some rural areas of Iraq during a period of February to August / 2017 and tested by using indirect-ELISA and PCR techniques. Overall results showed that 19.57% and 14.13% of sera and meat samples respectively were seropositive for anti-T. gondii-antibodies. In meat samples, the sero-prevalence was 7.61% and 14.13% in tissues of skeletal and cardiac muscles respectively. Regarding PCR technique, the total results showed that 5.44% and 1.09% of blood clots and meat extracts respectively were positive for DNA reaction of T. gondii. In addition, although the PCR results were found to be positive in cardiac muscles (1.09%) only, no significant differences had been detected regarding the results of skeletal muscles that lack positive cases. According to the diagnostic assays, significant differences in positive results were reported between indirect-ELISA and PCR technique among the tested samples of sera and meat as well as skeletal and cardiac muscles.Keywords: Toxoplasma gondii, Chickens, Blood, Meat, Serology, Molecular, Iraq.